Augustine's immanent critique of Stoicism. Issue 2 (19th April 2017) - Boersma, Gerald P.
Abstract: The broad contours of Augustine's critique of Stoic virtue theory in De civitate dei 19.4 finds a fascinating analogue in Theodor Adorno's theory of immanent critique: Augustine 'enters' into Stoic virtue theory and criticises it from its own postulates, illustrating the striking implausibility of Stoic orthodoxy when lived out in concreto and the absurd, but logical, conclusions to which one is necessarily carried by Stoic ethics. Through this deconstruction, Augustine clears a space to propose his own virtue ethic. Augustine maintains that a Stoic virtue ethic fails to deliver on its promised eudaimonistic ends because it lacks a robust eschatological vision. For Augustine, the Christian faith offers a more viable virtue ethic.